Grosse Strassenkämpfe in Berlin während des Generalstreiks. . 'Zerstörung durch [...] Minen i.d. Alten Schützenstrasse Berlin' (1919)
Grosse Strassenkämpfe in Berlin während des Generalstreiks. 'Zerstörung durch [...] Minen i.d. Alten Schützenstrasse Berlin'.